Estructura y funcionamiento de la familia homoparental en estudio de casos y planteamiento de acciones interventivas - Heras Romero, Denzel Jandir (Machala: Universidad Técnica de Machala, 2022)
Homoparental families have made their way through time in the traditional family context which, despite being governed by a heteronormative macho regime, have managed to become a more recurrent type of family in recent years. The formation of these families has been increasing due to the fact that the context has become more and more favorable, as homosexual persons have achieved the recognition of their rights, among them, the right to form a family and raise a child. There have even been advances and facilities in certain countries in the adoption or in vitro fertilization processes available to these families. However, very limited information is known about the family dynamics, structure, functioning and upbringing of children in these homes. In addition, most of the misinformation surrounding these households is born of homophobia that ends up translating into difficulties they must face in their daily lives. Therefore, this essay seeks to describe the structural and functional elements of homoparental families through literature review and case studies in order to have a better perspective and to be able to propose interventive actions. It was found that the most outstanding aspects are found in the structure and functioning, these families are governed by the welfare of the home rather than by traditional gender roles and that this is possible thanks to the priority they give to the use of dialogue, for these families communication is essential to function properly.
Las familias homoparentales a través del tiempo se han abierto paso en el contexto tradicional familiar que, a pesar de estar gobernado por un régimen heteronormativo machista han logrado convertirse en un tipo de familia más recurrente en los últimos años. La formación de estas ha venido en aumento debido a que el contexto cada vez se muestra más favorable, pues como personas homosexuales han logrado el reconocimiento de sus derechos, entre ellos, el derecho a formar una familia y criar un hijo. Incluso ha habido avances y facilidades en ciertos países en los procesos de adopción o fertilización in vitro que tienen a disposición estas familias. Sin embargo, se conoce información muy limitada acerca de la dinámica familiar, la estructura, funcionamiento y crianza de los hijos en estos hogares. Además, la mayor parte de la desinformación que rodea a estos hogares nace de la homofobia que termina traduciéndose en dificultades que deben afrontar en su vida cotidiana. Por ello este ensayo busca describir los elementos estructurales y de funcionamiento de las familias homoparentales a través de la revisión bibliográfica y estudio de casos para tener una mejor perspectiva y poder proponer acciones interventivas. Se obtuvo que los aspectos más sobresalientes se encuentran en la estructura y funcionamiento, estas familias se rigen por el bienestar del hogar más no por roles de géneros tradicionales y que esto es posible gracias a la prioridad que le dan al uso del diálogo, para estas familias la comunicación es indispensable para funcionar correctamente.
Keywords: ESTRUCTURA; HOMOPARENTALIDAD; FAMILIA; FUNCIONAMIENTO